Ethical-moral teaching strategies in Nursing students' training: an integrative review - Mireya Inés Triviños Barrientos; Dulcinéia Ghizoni Schneider; Maiara Suelen Mazera; Sylvia Jacqueline Álvarez Sandoval; Elide Mariela Alarcón Bustos (Universidade Federal do Ceará, 2024)
Objective: to synthesize the diverse scientific evidence about ethical-moral teaching strategies in Nursing students' training. Methods: an integrative review with search and selection of primary studies in six renowned data sources from the Health field, namely: Web of Science, MEDLINE/PubMed, CINAHL/EBSCO, LILACS, BDENF and SciELO, between 2018 and 2023. Results: the sample was comprised by 18 studies, selected from a universe of 784 articles. Two categories were generated after integrating the studies on Nursing students' ethical training; these categories associated strengthening the undergraduate students' knowledge, skills and attitudes and ethical-moral educational strategies. Conclusion: in Nursing training, it is necessary to encourage the development of moral skills and attitudes such as moral sensitivity, empathy, moral resilience and reasoning and ethical decision-making, as well as to incorporate professional values. Contributions to practice: this study contributes ethical-moral strategies for the development of ethical-moral skills in Nursing and to consolidate diverse knowledge and skills for ethical, humanistic and socially committed performance, involved with social justice and with defending life.